Papular atrichia - Lunge, Snehal B.; Vyshak, B. M. (International Journal of Research in Dermatology, 2020)
Congenital atrichia or papular atrichia is a rare form of irreversible alopecia inherited autosomal recessively. Atrichia congenita with papular lesions represents a complex and heterogeneous group of genodermatoses characterized by irreversible complete hair loss soon after birth, and associated with the development of keratin-filled cysts over the body. Mutation of the human hairless (HR) gene on chromosome 8p22 has been implicated with this condition. It has broad differential diagnosis and poses diagnostic and therapeutic challenges. We report an 8 year girl presenting with complete loss of hair over scalp, eye brows, eye lashes, and body soon after birth with papular lesions over face.